2020
DOI: 10.1124/jpet.120.266163
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimmune Mechanisms and Sex/Gender-Dependent Effects in the Pathophysiology of Mental Disorders

Abstract: Innate and adaptive immune mechanisms have emerged as critical regulators of CNS homeostasis and mental health. A plethora of immunologic factors have been reported to interact with emotion-and behavior-related neuronal circuits, modulating susceptibility and resilience to mental disorders. However, it remains unclear whether immune dysregulation is a cardinal causal factor or an outcome of the pathologies associated with mental disorders. Emerging variations in immune regulatory pathways based on sex differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 381 publications
(440 reference statements)
0
20
0
Order By: Relevance
“…In this study, we observed sex-related disparity in Ucp2 MGKO mice with female mice spared from alterations in network function and behavior. Although these differences may be attributed to divergent effects of steroid hormones on neuronal and microglial functions [ 49 ], there might be other factors that require detailed analysis in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed sex-related disparity in Ucp2 MGKO mice with female mice spared from alterations in network function and behavior. Although these differences may be attributed to divergent effects of steroid hormones on neuronal and microglial functions [ 49 ], there might be other factors that require detailed analysis in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we observed gender disparity in Ucp2 MGKO mice with female mice spared from alterations in network function and behavior. Although these differences may be attributed to divergent effects of steroid hormones on neuronal and microglial functions (32), there might be other factors that require detailed analysis in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Together with other mechanisms such as endogenous steroid levels, these differences may also underlie sexual dimorphism and left-right asymmetry in the hippocampus. Nevertheless, the hippocampus implicated in the etiology of several mental health disorders, many of which exhibit some degree of sex difference, and there are also subtle sex differences in hippocampal-associated behaviors such as spatial learning strategies and stress responsivity (Exner et al 2008;Frazier et al 2008;Kokkosis and Tsirka 2020;Krolick et al 2018).…”
Section: Discussionmentioning
confidence: 99%